2022
DOI: 10.18632/aging.203910
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction in mandibular hypoplasia, deafness and progeroid features with concomitant lipodystrophy (MDPL) patients

Abstract: Mandibular hypoplasia, Deafness and Progeroid features with concomitant Lipodystrophy is a rare, genetic, premature aging disease named MDPL Syndrome, due to almost always a de novo variant in POLD1 gene, encoding the DNA polymerase δ. In previous in vitro studies, we have already described several hallmarks of aging, including genetic damage, telomere shortening, cell senescence and proliferation defects. Since a clear connection has been reported between telomere shortening and mitochondria malfunction to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…We found that the immortalized cell lines from Pt#1, 2, and 16 (POLK) showed better metabolic capacity compared to control cell lines. Intriguingly, patients with mandibular hypoplasia, deafness and progeroid features with concomitant lipodystrophy, characterized by germline PGVs in POLD1, also present with mitochondrial dysfunction and metabolic abnormalities (15,47,48). Conversely, some familial RCC genes (such as FH, VHL, PBMR1, and SDHx) have also been implicated in suppression of DSBs and in replication stress (49)(50)(51)(52), based on mechanisms that are not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the immortalized cell lines from Pt#1, 2, and 16 (POLK) showed better metabolic capacity compared to control cell lines. Intriguingly, patients with mandibular hypoplasia, deafness and progeroid features with concomitant lipodystrophy, characterized by germline PGVs in POLD1, also present with mitochondrial dysfunction and metabolic abnormalities (15,47,48). Conversely, some familial RCC genes (such as FH, VHL, PBMR1, and SDHx) have also been implicated in suppression of DSBs and in replication stress (49)(50)(51)(52), based on mechanisms that are not well understood.…”
Section: Discussionmentioning
confidence: 99%